Effects of Coffea arabica on Streptococcus mutans adherence to dental enamel and dentine - de Oliveira, Luciane Dias [UNESP] (2007)
The aim of this study was to evaluate the effects of different coffee solutions on Streptococcus mutans adherence to human dental enamel and dentine. Seventy-five specimens of human enamel and 75 of dentine were included in the study. Coffee solutions were prepared with two different trade marks of coffee (Mellita® and Pilão®) and two methods of preparation. The specimens were divided into ten experimental groups (n-15) according to the coffee solution tested. Each specimen was transferred to cell culture plates containing offee solution and culture medium and 0.1 ml of Streptococcus mutans standardized suspension was inoculated into each well. After the period of incubation, the number of bacterial cells adhered to each specimen was obtained by plating method. Results were analyzed by ANOVA and Tukey's test (5%). Results showed that Streptococcus mutans adherence was statistically lower in the presence of the solution obtained by boiling method and the trade mark PilãÔ (p-0.00) when compared with the other groups. All the test-groups presented values of cfu/ml significantly lower in relation to the control groups (p=0.00). It could be concluded, within the conditions of the study, that the coffee solutions tested reduced significantly the adherence of Streptococcus to dental enamel and dentine.